Logics of empowerment : development, gender, and governance in neoliberal India - Sharma, Aradhana (University of Minnesota Press, 2008)
Celebratory news features about India's thriving middle class tell only part of the story of the country's recent economic rise, frequently glossing over the 300 million Indians who live on the margins and struggle to survive under economic liberalization. How do those cast out of their country's successes perceive and respond to their position and mobilize against disempowerment? In Logics of Empowerment, Aradhana Sharma takes up these questions, focusing on the work of an innovative women's program called Mahila Samakhya that is part governmental and part nongovernmental and strives to empow.